Pour une critique et une reconstruction féministes de l’éducation thérapeutique. L’exemple de l’endométriose - Anaïs Choulet-Vallet (Éducation et Socialisation)
The therapeutic education of the patients (TEP) has been developing over the last twenty years in response to the changes brought by the increase in chronic illnesses. The goal of this method is to involve patients in their therapeutic path and to operationalize care. While this system is based on the autonomy of sick people, it places a greater emphasis on the role of healers. This paradox is the result of three blind spots: 1. TEP assumes that patient is rational. 2. TEP considers the care relationship in a unilateral way. 3. TEP underestimates the socio-political roots of health education. In order to compensate for the misuse of therapeutic education, this article proposes a feminist appraisal. And to give consistency to this assessment, this study uses the example of endometriosis.